2006
DOI: 10.1002/chem.200600258
|View full text |Cite
|
Sign up to set email alerts
|

Valence Tautomerism in Octahedral and Square‐Planar Phenoxyl–Nickel(II) Complexes: Are Imino Nitrogen Atoms Good Friends?

Abstract: The two tetradentate ligands H2L and H2LMe afford the slightly distorted square‐planar low‐spin NiII complexes 1 and 2, which comprise two coordinated phenolate groups. Complex 1 has been electrochemically oxidized into 1+, which contains a coordinated phenoxyl radical, with a contribution from the nickel orbital. In the presence of pyridine, 1+ is converted into 1Py+, an octahedral phenolate nickel(III) complex with two pyridines axially coordinated: An intramolecular electron transfer (valence tautomerism) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
126
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 74 publications
21
126
3
Order By: Relevance
“…The five-line superhyperfine pattern in the highfield component is assigned to two equivalent pyridine ligands axially bound to the Ni III center to form 1-py 2 + . Similarly to the findings of others, [6,7] axial coordination of pyridine to 1 + shifts the d z 2 orbital to higher energy, resulting in the transfer of an electron from the metal center to the ligand. Computational studies on 1-py 2 + ( Figure S4 in the Supporting Information) demonstrate an increase in spin density on Ni from 0.15 (for 1 + ) to 0.93, which is consistent with this shift in the locus of oxidation.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…The five-line superhyperfine pattern in the highfield component is assigned to two equivalent pyridine ligands axially bound to the Ni III center to form 1-py 2 + . Similarly to the findings of others, [6,7] axial coordination of pyridine to 1 + shifts the d z 2 orbital to higher energy, resulting in the transfer of an electron from the metal center to the ligand. Computational studies on 1-py 2 + ( Figure S4 in the Supporting Information) demonstrate an increase in spin density on Ni from 0.15 (for 1 + ) to 0.93, which is consistent with this shift in the locus of oxidation.…”
Section: Methodssupporting
confidence: 57%
“…Temperature-dependent valence tautomerism has also been reported for 2 + [7,8] and 3 + , [6] whereas the analogous complex 4 + [10] was found to be a ligand radical in the range 10-295 K. Recent reports have suggested that these tautomeric shifts are associated with axial binding of water or other impurities at the solvent freezing point, rather than a shift in the locus of oxidation due to temperature alone. [8,10] In an effort to understand this process further, a solution of 1 + in the presence of a 100-fold excess of tetrabutylammonium perchlorate (TBAP) was studied by EPR spectroscopy (Figure 3 b).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The solid spectrum shows a notable difference respecting precursor (Figure 3). The band LMCT at 459 nm is notably red shifted from 1 (449 nm), similar to similar systems [23]. Three more bands were observed at 571, 886, 922 and 955 nm, which were assigned to the transitions…”
Section: Preparation Ofsupporting
confidence: 71%
“…The valence state difference dependent on solvents can be considered to be due to coordination of DMF molecules to the nickel ion. Addition of exogenous ligands such as pyridine to the CH2Cl2 solution of [Ni(Salcn)] + causes the color change from green to purple, and the solution showed the UV-vis absorption spectrum and EPR signals characteristic of Ni(III) complexes [63,64]. Further, the X-ray crystal structure of -oxo Ni III (salen) dimer has been reported to be synthesized by addition of excess O2 under basic conditions ( Figure 13) [55].…”
Section: Characterization Of One-electron Oxidized M(ii) Salen-type Cmentioning
confidence: 99%